2019
DOI: 10.3390/ijms20020324
|View full text |Cite
|
Sign up to set email alerts
|

The microRNAs Regulating Vascular Smooth Muscle Cell Proliferation: A Minireview

Abstract: Vascular smooth muscle cell (VSMC) proliferation plays a critical role in atherosclerosis. At the beginning of the pathologic process of atherosclerosis, irregular VSMC proliferation promotes plaque formation, but in advanced plaques VSMCs are beneficial, promoting the stability and preventing rupture of the fibrous cap. Recent studies have demonstrated that microRNAs (miRNAs) expressed in the vascular system are involved in the control of VSMC proliferation. This review summarizes recent findings on the miRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 99 publications
(136 reference statements)
3
42
0
1
Order By: Relevance
“…HDLs are highly heterogeneous and transport a large variety of lipids, proteins, and microRNAs [86]. Anti-sense nucleotides and siRNA(s) are widely used to modulate gene expression and are being considered for therapeutics of atherosclerosis [87][88][89]. One of the major issues is that the half-life of anti-sense nucleotides is usually low in the presence of serum nucleases [90].…”
Section: Delivery Of Oligonucleotides Using Rhdl Nanoparticlesmentioning
confidence: 99%
“…HDLs are highly heterogeneous and transport a large variety of lipids, proteins, and microRNAs [86]. Anti-sense nucleotides and siRNA(s) are widely used to modulate gene expression and are being considered for therapeutics of atherosclerosis [87][88][89]. One of the major issues is that the half-life of anti-sense nucleotides is usually low in the presence of serum nucleases [90].…”
Section: Delivery Of Oligonucleotides Using Rhdl Nanoparticlesmentioning
confidence: 99%
“…Vascular smooth muscle cell-associated miRNAs were selected from disease-miRNA interactions validated in previous studies (Leeper and Maegdefessel, 2018;Wang and Atanasov, 2019). For the obtained VSMC-related miRNAs, we predicted whether there was a regulatory relationship between them and the selected differentially expressed circRNAs.…”
Section: Interaction Between Circrna and Mirnamentioning
confidence: 99%
“…miRNAs have been shown to target numerous transcription factors, signalling cascades and growth factors that regulate VSMC proliferation ( Figure 2) [91]. A recent study conducted in SMCs isolated from human saphenous veins showed that miR-21 overexpression increases the proliferative capacity of these cells and drives the switch towards a more synthetic phenotype [92].…”
Section: Vascular Smooth Muscle Cell Proliferation and Differentiationmentioning
confidence: 99%